New records of Haemagogus (Haemagogus) from Northern and Northeastern Brazil (Diptera: Culicidae, Aedini) - Alencar, Jerônimo; Castro, Francisco C.; Monteiro, Hamilton A. O.; Silva, Orlando V.; Dégallier, Nicolas; Marcondes, Carlos Brisola; Guimarães, Anthony E. (Zootaxa, 2008)
Haemagogus (Haemagogus) is restricted mostly to the Neotropical Region, including Central America, South America and islands (Arnell, 1973). Of the 24 recognized species of this subgenus, 15 occur in South America, including the Antilles. However, the centre of distribution of the genus Haemagogus is Central America, where 19 of the 28 species (including four species of the subgenus Conopostegus Zavortink [1972]) occur (Arnell, 1973).